Figurative Languages in The Shape of Water Movie - fadilah, fadilah; Nurhayati S (Universitas Nasional, 2024)
Films, as literary works, use numerous types of language to communicate meaning, provoke emotions, and tell stories successfully. The auditory and symbolic elements are part of the languages associated with figurative language that refers to written or spoken communication, its principles and effects can also be applied in visual storytelling, which is a key aspect of the film itself. Understanding figurative language in a movie is a challenge for language enthusiasts as it involves interpretation and awareness of cultural and contextual influences on meaning. This study, exploring the use of figurative language in ‘The Shape of Water’ movie, employed a descriptive qualitative approach, which provides a factual and accurate description of the issue or area of interest. The study found that the film used seven language styles: personification, metaphor, simile, euphemism, metonymy, and allegory. Each figure of speech appears in varying quantities, In addition, there were fifteen sentences out of forty-six data containing similes which means people are most familiar with similes in literary works, notably in movies.